2020
DOI: 10.1364/oe.402447
|View full text |Cite
|
Sign up to set email alerts
|

Reference-free THz-TDS conductivity analysis of thin conducting films

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Recently, it has been shown that it is also possible to perform reference-free extraction of dielectric and electrical properties of substrates and thin conducting films from THz-TDS measurements [28,29]. This is achieved by comparing individual transients from only the sample waveform, which means that the reference measurement can be omitted and furthermore decreases errors from signal fluctuations originating from the measurement setup such as timing jitter [26], periodic sampling errors [30], and uneven stage movement.…”
Section: Thz-tds Measurement Schemesmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, it has been shown that it is also possible to perform reference-free extraction of dielectric and electrical properties of substrates and thin conducting films from THz-TDS measurements [28,29]. This is achieved by comparing individual transients from only the sample waveform, which means that the reference measurement can be omitted and furthermore decreases errors from signal fluctuations originating from the measurement setup such as timing jitter [26], periodic sampling errors [30], and uneven stage movement.…”
Section: Thz-tds Measurement Schemesmentioning
confidence: 99%
“…It is possible to determine d sub from the distance between peaks in frequency domain from the Fourier transform of the full THz waveform including all transients. In practice, the correction terms for the amplitude and Gouy phase shift can be determined from one single calibration-like measurement [29]. This is advantageous compared to the standard referenced analysis in equations ( 1)-( 3), where reference measurements must be acquired frequently to minimize effects from environment, mechanical stage movement and THz source fluctuations, all of which have no influence on the reference-free analysis.…”
Section: Thz-tds Measurement Schemesmentioning
confidence: 99%
See 3 more Smart Citations